Legislative obstruction: how to do it? - Humphreys, Richard F
This article examines the practical mechanics of obstructing legislation in Ireland. It does not directly deal with the obstruction of Parliamentary business other than legislation, although many of the techniques used in the context of legislation could be equally applied to other forms of non-legislative business. Three primary forms of obstruction of legislation namely; postponement, interruption and prolongation of business are discussed
Keywords: Legislative Procedure; Legislative Obstruction - Ireland